From coastline to feed trough: unlocking Palmaria palmata feed potential for monogastric farm animals - Khattak, Farina; Mkrtchyan, Hermine V.; Smallman, Duncan; Estridge, Patricia; Allen, Michael J.; Short, Fiona; Sutcliffe, Martin; Houdijk, Jos G. M. (Frontiers in Animal Science, 2025)
Palmaria palmata (P. palmata), commonly known as Dulse, is a red seaweed with increasing relevance as a potential sustainable feed ingredient for monogastric animals. It provides balanced proteins, essential amino acids, minerals, and diverse bioactive compounds with potential antioxidant and immunomodulatory effects. Unlike conventional protein sources, it can be cultivated without competing for arable land or freshwater, aligning with the goals of a circular economy. However, challenges include compositional variability, seasonal and geographic influences, and risks of contaminants such as heavy metals, iodine, and microbial hazards. Feeding trials in non-ruminants demonstrate that inclusion is feasible without adverse effects and may improve gut health and product quality; however, the evidence remains limited in scope and duration. This review consolidates current knowledge on the nutritional composition, bioactive compounds, safety concerns, processing technologies, and feeding outcomes of P. palmata, highlighting evidence gaps for safe inclusion levels, optimised processing, hazard management, and sustainability evaluation.